2015
DOI: 10.1016/j.jse.2014.12.029
|View full text |Cite
|
Sign up to set email alerts
|

Effect of scapular dyskinesis on supraspinatus repair healing in a rat model

Abstract: Background Rotator cuff tears are common conditions that often require surgical repair to improve function and relieve pain. Unfortunately, repair failure remains a common problem following rotator cuff repair surgery. Several factors may contribute to repair failure including age, tear size, and time from injury. However, the mechanical mechanisms resulting in repair failure are not well understood making clinical management difficult. Specifically, altered scapular motion (termed scapular dyskinesis) may be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…215 Lastly, scapular dyskinesis, as induced through transection of the accessory and long thoracic nerves, decreased mechanical properties, altered histology, and diminished tendon organization at the enthesis following rotator cuff repair. 216 Taken together, these studies validate the importance of controlled mobilization postoperatively as a means to optimize healing. In the clinical setting, where the practical postoperative loading protocols have been far more constrained than those investigated in animal studies, there is no long-term difference between early mobilization compared to delayed rehabilitation.…”
Section: Mechanical Loading In the Context Of Tissue Engineeringmentioning
confidence: 64%
“…215 Lastly, scapular dyskinesis, as induced through transection of the accessory and long thoracic nerves, decreased mechanical properties, altered histology, and diminished tendon organization at the enthesis following rotator cuff repair. 216 Taken together, these studies validate the importance of controlled mobilization postoperatively as a means to optimize healing. In the clinical setting, where the practical postoperative loading protocols have been far more constrained than those investigated in animal studies, there is no long-term difference between early mobilization compared to delayed rehabilitation.…”
Section: Mechanical Loading In the Context Of Tissue Engineeringmentioning
confidence: 64%
“…The collagen architecture of the insertion is also interdigitated . While there have been numerous excellent studies of rotator cuff degeneration/injuries in rats, genetic perturbations are difficult to achieve in rats due to the paucity of available molecular tools. Recently, a few groups established models of clinically relevant supraspinatus tendon injuries in the mouse, thus opening the door for mechanistic studies enabled by the wide array of genetic tools available for mouse.…”
mentioning
confidence: 99%
“…through improved scapular muscle balance (Merolla et al, 2010). The recent works of Reuther et al (2014Reuther et al ( , 2015 on an animal model also support a causative effect. Whatever the cause-effect relationship, it was shown that dyskinesis deeply affects functional scores (Harris et al, 2012), and it should always be evaluated and accounted for during rehabilitation.…”
Section: Discussionmentioning
confidence: 77%